Uma leitura de lugar em patrimônio histórico na era digital: experiências instagramáveis na área do Anel Viário em São Luís-Maranhão - ROCHA, Nathália Christine Garcez (2024)
The mass use of technology confirms the popular saying: “to remember is to live”, every time photos of places are shared on social networks a message is transmitted between interlocutors. In the era of “digital positioning” it is useful to understand the way in which the population interacts with places, as in just a few hours on the networks it is possible to perceive the number of records of places sometimes described as perfect; New terms such as “instagrammable” places are recurrent in internet users’ dialogue. But, in real life, how do these people relate to these places? This work aims to understand how the idea of historical heritage fits into the contemporary digital era, specifically identifying the Instagrammable experiences of users of listed public spaces in São Luís do Maranhão, a section of Avenida Senador Vitorino Freire, due to its connection with significant urban facilities of Maranhão culture such as: Capela de São Pedro, Passarela do Samba, Centro de Comercialização de Produtos Sananais do Maranhão, Parque São João Paulo II and the popular Anel Viário which has undergone a significant urban renovation, since 2018, in Fonte do Bispo Terminal and Urban Park, which was completed in 2023. With the aim of understanding how interventions at this level affect everyday dynamics, awakening the feeling of belonging and people's relationship with public spaces and, in Specially, those inserted in an area of historical and cultural value of reference for the city, this work is based on the ideas of space, place and the feeling of belonging that so much seeks to achieve after urban intervention works, especially those carried out in centers histories that lack vitality without losing the values they carry.